Bioaccumulation of Some Heavy Metals in Ayre Fish (Sperata Aor Hamilton, 1822), Sediment and Water of Dhaleshwari River in Dry Season (Bangladesh Journal of Zoology, 2012)
The present study was carried out to determine the level of bioaccumulation of some heavy metals in a freshwater fish Ayre (Sperata aor Hamilton, 1822) collected from Rajfulbaria (23°48?56.36? N and 90°14?54.04? E) of  Dhaleshwari river. Four heavy metals, namely chromium (Cr), copper (Cu), lead (Pb), and cadmium (Cd) were selected for this study. Metal concentrations were   determined by Flame Atomic Absorption Spectrophotometer after nitric acid  digestion of samples. The concentrations of accumulated heavy metals in fish were  also compared with the concentrations of metals in the sediments and waters of  that river. The level of bioaccumulations in different organs of S. aor were determined separately and compared among them. Average bioaccumulation levels  in S. aor were Cr: 1.458 mg/kg, Cu: 31.500 mg/kg, Pb: 18.776 mg/kg and Cd:  0.487 mg/kg of dry weight. The levels of heavy metals in sediments were Cr: 27.393 mg/kg, Cu: 37.450 mg/kg, Pb: 15.797 mg/kg and Cd: 2.083 mg/kg, and in water were Cr: 0.130 ppm, Cu: 0.000 ppm, Pb: 0.201 ppm and Cd: 0.001 ppm.The bioaccumulation of these four heavy metals in fish organs, sediment and  water samples were also compared with FAO approved standard levels and other  related studies, and found that the levels of bioaccumulation in the Dhaleshwari river exceeded all the standard levels. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12904 Bangladesh J. Zool. 40(1):147-153, 2012